Effect of mediterranean diet on breast cancer: meta-analysis - Demirci, Ülkü; Karaağaç, Rabia Melda; Pınarlı Falakacılar, Çağla; Kaptanoğlu, Ayşe (My University, 2024)
Objective: In this meta-analysis, we have assessed the effects of Mediterranean Diet on breast cancer. Methods: Case-control and cross-sectional studies were searched using PubMED, SpringerLink, and Taylor & Francis databases for inclusion in the meta-analysis. We confined our search to the studies conducted and published after year 2000. From all the included studies, geography, sample size, study design, study evaluation method, outcome, risk factors (lowest and highest limit and OR values), and 95% confidence interval data were extracted. Eleven studies with 26361 participants were included of which 10 were case-control studies and 1 was cross-sectional study. Results: Following the analysis according to the random effects model, it was observed that compliance with the Mediterranean Diet or the high consumption amount of olive oil, seafood, whole grains, vegetables, and fruits in the Mediterranean Diet has a positive effect on breast cancer. The effect size was found to be OR 0.77 (0.68-0.88). Conclusion: This meta-analysis, including the studies evaluating the effect of Mediterranean diet on breast cancer, concluded that the Mediterranean Diet has positive effects on breast cancer. The risk of breast cancer was found to be decreased with the increased compliance of the Mediterranean Diet.
Keywords: Breast Cancer; Cross-Sectional Study; Mediterranean Diet